Preoperative Predictors of Poor Outcomes Following Lumbar Discectomy. A Study based on the National Finspine Registry - Saarinen, Antti; Suominen, Eetu; Pekkanen, Liisa; Malmivaara, Antti; Huttunen, Jukka; Pernaa, Katri; Salo, Henri; Repo, Jussi P. (Ovid Technologies (Wolters Kluwer Health), 2025)
Study design: Retrospective cohort study.
Objective: To identify predictors for poor outcome after lumbar discectomy for herniated disc.
Summary of background data: Lumbar discectomy for herniated disc is a common spinal procedure. Despite the surgical treatment, some patients are left with persistent pain and poor health-related quality of life. We aim to research preoperative predictive factors associated with poor outcome after lumbar discectomy.
Methods: National spine surgery registry was searched for patients who underwent primary discectomy for lumbar disc herniation between 2017 and 2022. All patients had a minimum of 2 years of follow-up. The primary outcome was disability at 12 months postoperatively, assessed using the Oswestry Disability Index (ODI). Patients were categorized into satisfactory (ODI 0-40) and poor outcome groups (ODI 41-100). Logistic regression was used to identify preoperative predictors of poor outcome. Variables for multivariable analysis were selected based on clinical relevance assessed by senior authors and bivariate associations. Secondary outcomes included pain scores and patient-reported satisfaction.
Results: In all, 3339 patients were included, of whom 2991 (90%) had minimal to moderate disability and 348 (10%) had severe disability assessed with ODI at the follow-up. Several factors were identified to associate with poor outcome after the surgery: older age (OR 1.03,95%CI 1.02-1.03), female sex (OR 1.28,95%CI 1.03-1.61), higher body mass index (OR 1.06,95%CI 1.02-1.09), cardiologic comorbidity (OR 4.27,95%CI 2.4-7.3), regular preoperative painkiller use (OR 2.2,95%CI 1.5-3.3), and higher number of operated vertebrae (OR 2.4,95%CI 1.6-3.6). Symptom lasting over one year was associated with worse outcomes when compared with symptoms for 3-12 months (OR 0.42,95%CI 0.29-0.60), 6-12 weeks (OR 0.23,95%CI 0.12-0.39), and those with symptoms for less than 6 weeks (OR 0.35,95%CI 0.19-0.62). Employed individuals were significantly associated with better outcomes when compared other statuses. Worse preoperative quality of life scores was associated with poor outcome.
Conclusion: Several preoperative factors were associated with poor outcome after lumbar discectomy. Identifying higher-risk patients - such as those with high BMI, older age, or significant comorbidities - can support preoperative counseling and targeted interventions. Optimizing modifiable factors preoperatively may improve outcomes.